Furthering the sceptical case against virtue ethics in nursing ethics - Holland, Stephen (Nursing philosophy, 2012)
In a recent article in this journal I presented a sceptical argument about the current prominence of virtue ethics in nursing ethics. Daniel Putman has responded with a defence of the relevance of virtue in nursing. The present article continues this discussion by clarifying, defending, and expanding the sceptical argument. I start by emphasizing some features of the sceptical case, including assumptions about the nature of sceptical arguments, and about the character of both virtue ethics and nursing ethics. Then I respond to objections of Putman's such as that, according to virtue ethics, virtue is relevant to the whole of a human life, including one's behaviour in a professional context; and that eudaimonia should be central in explaining and motivating a nurse's decision to enter the profession. Having argued that these objections are not compelling, I go on to discuss an interesting recent attempt to reassert the role of virtue ethics in the ethics of professions, including nursing. This centres on whether role-specific obligations - e.g. the obligations that arise for a moral agent qua lawyer or mother - can be accommodated in a virtue ethics approach. Sean Cordell has argued that the difficulty of accommodating role-specific obligations results in an ‘institution-shaped gap’ in virtue ethics. He suggests a way of meeting this difficulty that appeals to the ergon of institutions. I endorse the negative point that role-specific obligations elude virtue ethics, but argue that the appeal to the ergon of institutions is unsuccessful. The upshot is further support for scepticism about the virtue ethics approach to nursing ethics. I end by gesturing to some of the advantages of a sceptical view of virtue ethics in nursing ethics.